Algoritmos para o Cálculo de Estruturas de Proteínas - Silva, Warley Gramacho da (2008)
One of the most important problems in computational biology is the determination of the three-dimensional structure of a protein. This structure can be determined experimentally using NMR techniques. Generally, the NMR data provide only a sparse set of distances between atoms in a molecule. In this case the problem is to determine the three-dimensional structure of a molecule using a set of distances between certain pairs of atoms of the molecule, and is known as the molecular distance geometry problem which is generally expressed as a problem of continuous optimization. However, conditions for dealing with it as a combinatorial optimization problem were presented recently in the literature by using a discrete formulation. Two algorithms and two softwares for visualizing are proposed in this work. In order to test the algorithms we have used real and artificial instances